Systematic review of the advantages of trichloroacetic acid and electrocautery therapy in verruca vulgaris - Kamilah, Lian; Adjie, Sugih Primas; Dharmawan, Nugrohoaji (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2025)
Verruca vulgaris (VV), a cutaneous disorder associated with human papillomavirus (HPV), presents as a benign proliferation of keratinocytes. Verruca vulgaris therapy with destructive methods such as trichloroacetic acid (TCA) and electrocautery is the most commonly used therapeutic modality. The study aims to assess the therapeutic efficacy and clinical benefit of trichloroacetic acid (TCA) and electrosurgery in managing VV by synthesising evidence from clinical studies or case series. Systematic review adhered to the guidelines outlined in the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA). To ensure the collection of accurate and relevant information, literature searches were conducted across PubMed, Google Scholar and Cochrane Library covering publications from 2014 to 2023. Twelve studies were included, comprising eight articles on TCA and four articles on electrosurgery. Trichloroacetic acid achieved a maximum cure rate of 93.3% while electrosurgery reached 100%. During six-month follow-up period, TCA showed no recurrence (0%), whereas electrosurgery had a recurrence rate of 21,9%. Electrocautery has more advantages than TCA with a higher cure rate. Even though it has a higher cure rate, electrocautery has a higher recurrence rate with more severe side effects than TCA.